Analisis Pengaruh U-Turn Terhadap Kinerja Jalan William Iskandar Kabupaten Deli Serdang dengan Simulasi PTV VISSIM - Harahap, Anggi Ramadhani Kamalia; Alfiani, Alfiani; Amrizal, Amrizal (PT. Arsil Reka Engineering, 2026)
The rapid growth in population density and economic activities in Deli Serdang Regency has increased traffic demand beyond the available road capacity, particularly on William Iskandar Pasar V Road, where a U-turn facility affects traffic operations. The presence of this facility reduces vehicle speed, increases queuing, and decreases road performance. This study was conducted based on the Indonesian Highway Capacity Guidelines (PKJI) 2023, the Regulation of the Minister of Transportation No. 96 of 2015 concerning Road Level of Service, and the 2005 U-turn Planning Guidelines to evaluate road performance and identify appropriate improvement alternatives. Primary data, including traffic volume, side friction, speed, and road geometry, were collected through field surveys over seven days during peak hours. The data were analyzed using PKJI 2023 and simulated with PTV VISSIM. The results indicate that the highest degree of saturation reached 1.35 on weekdays, corresponding to Level of Service F, with considerable delays and long queues for U-turning vehicles. The VISSIM model was validated with a GEH value of 3.565. The findings suggest that relocating the U-turn opening, providing a dedicated U-turn lane, widening the outer lane, and reducing side friction can improve traffic flow and road performance.